Microbiological safety of cosmetic products and potential risks for consumers - Krajišnik Danina; Đekić Ljiljana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2018)
The European regulatory framework in the field of cosmetic products requires of manufacturers to provide an assessment of microbial limits tests and results of preservation challenge test, as well as microbiological stability data which should be documented in the cosmetic product safety report. During the development of a cosmetic product, it is necessary to consider the risk of microbiological contamination in the selection of starting cosmetic ingredients and packaging, manufacturing process, alongside with conditions of storage and use. The deviation of the microbiological quality of the cosmetic product from the manufacturer's specification presents a risk for consumers, especially if it is used around the eyes, on mucous membranes in general, on damaged skin or it is intented for use in specific groups of consumers (children under the age of 3, elderly people and immunocompromised persons).